Growth and yield in plant crop of bananas 'Prata Anã' (AAB) at seven spacings - Pereira, Marlon Cristian Toledo; Salomão, Luiz Carlos Chamhum; Silva, Sebastião de Oliveira e; Sediyama, Carlos Sigueyuki; Couto, Flávio Alencar D'Araújo; Neto, Sebastião Pedro da Silva (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this study was to evaluate the behavior of 'Prata Anã' banana (Musa spp.) in the plant crop, in Jaíba, MG, Brazil, submitted to seven spacings, in irrigated culture. The treatments were: triangle: 2.7 m x 3.2 m (1,157 holes/ha) and 2.9 m x 3.4 m (1,014 holes/ha); double row in triangle: 4.5 m x 2.0 m x 3.0 m (1,026 holes/ha) and 4.5 m x 2.0 m x 2.0 m (1,538 holes/ha); double row in rectangle: 4.5 m x 2.0 m x 3.5 m (879 holes/ha); and rectangle: 4.0 m x 2.0 m (1,250 holes/ha) and 3.0 m x 2.0 m (1,666 holes/ha). The systems of spacing and populational densities tested did not influence neither the rate of growth of the plants nor the plant characteristics at harvest time. However, the productivity was greater for the bananas planted at greater densities, up to 29.1 ton/ha. The plants showed, in average, cycle from plantation to harvest time of 411 days, cycle from flowering to harvest time of 141 days and bunches with 17.7 kg, 9.1 hands and 134 fingers. The most suitable spacing for the region of Jaíba is 3.0 m x 2.0 m in rectangle, in the plant crop.